BACE1 modulates gating of KCNQ1 (Kv7.1) and cardiac delayed rectifier KCNQ1/KCNE1 (IKs). (December 2015) - Agsten, Marianne; Hessler, Sabine; Lehnert, Sandra; Volk, Tilmann; Rittger, Andrea; Hartmann, Stephanie; Raab, Christian; Kim, Doo Yeon; Groemer, Teja W.; Schwake, Michael; Alzheimer, Christian; Huth, Tobias
Abstract: KCNQ1 (Kv7.1) proteins form a homotetrameric channel, which produces a voltage-dependent K + current. Co-assembly of KCNQ1 with the auxiliary β-subunit KCNE1 strongly up-regulates this current. In cardiac myocytes, KCNQ1/E1 complexes are thought to give rise to the delayed rectifier current IKs, which contributes to cardiac action potential repolarization. We report here that the type I membrane protein BACE1 (β-site APP-cleaving enzyme 1), which is best known for its detrimental role in Alzheimer's disease, but is also, as reported here, present in cardiac myocytes, serves as a novel interaction partner of KCNQ1. Using HEK293T cells as heterologous expression system to study the electrophysiological effects of BACE1 and KCNE1 on KCNQ1 in different combinations, our main findings were the following: (1) BACE1 slowed the inactivation of KCNQ1 current producing an increased initial response to depolarizing voltage steps. (2) Activation kinetics of KCNQ1/E1 currents were significantly slowed in the presence of co-expressed BACE1. (3) BACE1 impaired reconstituted cardiac IKs when cardiac action potentials were used as voltage commands, but interestingly augmented the IKs of ATP-deprived cells, suggesting that the effect of BACE1 depends on the metabolic state of the cell. (4) The electrophysiological effects of BACE1 on KCNQ1 reported here were independent of its enzymatic activity, as they were preserved when the proteolytically inactive variant BACE1 D289N was co-transfected in lieu of BACE1 or when BACE1-expressing cells were treated with the BACE1-inhibiting compound C3. (5) Co-immunoprecipitation and fluorescence recovery after photobleaching (FRAP) supported our hypothesis that BACE1 modifies the biophysical properties of IKs by physically interacting with KCNQ1 in a β-subunit-like fashion. Strongly underscoring the functional significance of this interaction, we detected BACE1 in human iPSC-derived cardiomyocytes and murine cardiac tissue and observed decreased IKs in atrial cardiomyocytes of BACE1-deficient mice. Highlights: BACE1-deficient mice show reduced IKs in murine atrial cardiomyocytes. The β-secretase BACE1 was detected in human iPSC-derived cardiac myocytes. BACE1 physically interacts with KCNQ1 channels in a β-subunit-like fashion. Effects of BACE1 on reconstituted IKs (KCNQ1/E1) depend on cytosolic ATP level.